Technical Information Sources : a guide to patents standards and technical reports literature - Fla, Bernard Houghton; National Library of Australia, Canberra; National Library of Australia, Canberra (Melbourne : F. W. Cheshire, 1967)
This publication seeks to bring together sufficient details of information sources relating to the technical and scientific needs of industry so that workers can identify the most appropriate source for a given problem. Produced under the guidance of the Australian Industry Information Network Liaison Committee convened by the National Library of Australia, it contains 775 entries arranged by state or territory. Each entry provides the name and address of the institution, the name of the person to be contacted, a description of the subject fields covered, the library holdings (if any), and the consultancy services available. A subject index, data base and publications index, and an organization index are appended. (Author/JAB)
ERIC Note: Development of Resource Sharing Networks Study Series.
Microfiche.
Keywords: Information Storage & Retrieval System; Australia; Reports, Research